Primordial Dwarfism Gene Maintains Lin28 Expression to Safeguard Embryonic Stem Cells from Premature Differentiation - Qian Dai; Guangxin Luan; Li Deng; Tingjun Lei; Han Kang; Xu Song; Yujun Zhang; Zhi-Xiong Xiao; Qintong Li (Cell Reports, 2014)
Primordial dwarfism (PD) is characterized by global growth failure, both during embryogenesis and postnatally. Loss-of-function germline mutations in La ribonucleoprotein domain family, member 7 (LAPR7) have recently been linked to PD. Paradoxically, LARP7 deficiency was previously assumed to be associated with increased cell growth and proliferation via activation of positive transcription elongation factor b (P-TEFb). Here, we show that Larp7 deficiency likely does not significantly increase P-TEFb activity. We further discover that Larp7 knockdown does not affect pluripotency but instead primes embryonic stem cells (ESCs) for differentiation via downregulation of Lin28, a positive regulator of organismal growth. Mechanistically, we show that Larp7 interacts with a poly(A) polymerase Star-PAP to maintain Lin28 mRNA stability. We propose that proper regulation of Lin28 and PTEFb is essential for embryonic cells to achieve a sufficient number of cell divisions prior to differentiation and ultimately to maintain proper organismal size.